2019
DOI: 10.3803/enm.2019.34.4.382
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Glycemic Control with Once-Daily Insulin Degludec/Insulin Aspart after Changing from Basal Insulin in Adults with Type 2 Diabetes

Abstract: BackgroundConflicting results have been reported on the efficacy of insulin degludec/insulin aspart (IDegAsp) compared to basal insulin in type 2 diabetes. We investigated the effects of changing basal insulin to IDegAsp on glycemic control and sought to identify factors related to those effects.MethodsIn this retrospective study of patients from three referral hospitals, patients with type 2 diabetes using basal insulin with hemoglobin A1c (HbA1c) levels less than 11.0% were enrolled. Basal insulin was replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…The literature search yielded 921 potentially relevant articles (PubMed 154, EMBASE 295, and Cochrane Library 472), of which 719 were screened for title and abstract after excluding 202 duplicate articles. Thereafter, 674 articles that did not meet the inclusion criteria were excluded, and the remaining 45 studies were evaluated for eligibility by performing a full-text review; finally, 17 studies [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] with 3831 participants were included in this meta-analysis ( Figure 1 ). The effect on glycemic control and the risk of hypoglycemia development with those on the twice-daily IDegAsp regimen were reported in eight studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], while those on the once-daily regimen were reported in nine studies [ 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search yielded 921 potentially relevant articles (PubMed 154, EMBASE 295, and Cochrane Library 472), of which 719 were screened for title and abstract after excluding 202 duplicate articles. Thereafter, 674 articles that did not meet the inclusion criteria were excluded, and the remaining 45 studies were evaluated for eligibility by performing a full-text review; finally, 17 studies [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] with 3831 participants were included in this meta-analysis ( Figure 1 ). The effect on glycemic control and the risk of hypoglycemia development with those on the twice-daily IDegAsp regimen were reported in eight studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], while those on the once-daily regimen were reported in nine studies [ 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…We classified one RCT with a serious risk of bias as we used the data to only determine the switch from once-daily basal insulin to once-daily IDegAsp [ 23 ]. Three trials with a one-group pretest–post-test design demonstrated a serious risk of bias [ 13 , 14 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…IDegAsp serves as a simple and adaptive treatment option requiring only a single injection that can reveal a better alternative to achieve a higher standards of patients' lifestyle and QoL in comparison with more complex alternatives, with a lower frequency of daily injections (in comparison with the basal-bolus and premixed regimens), which is more likely to be perceived and recognized as less burdensome by patients [7,21,22]. By means of switching to IDegAsp in our study, the median of daily insulin administration frequency applied by the participants decreased from 4 to 2.…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest the article by Jang et al [1], entitled "Favorable glycemic control with once-daily insulin degludec/insulin aspart after changing from basal insulin in adults with type 2 diabetes." In the absence of high-level clinical evidence for insulin users in Korea, the study provided new insights for clinical researchers studying diabetes mellitus (DM).…”
mentioning
confidence: 99%